Acute and chronic central nervous system oxidative stress/toxicity during hyperbaric oxygen treatment of subacute and chronic neurological conditions - Harch, Paul G.; Rhodes, Stacey (Frontiers in Neurology, 2024)
Introduction Oxygen toxicity has been defined as acute central nervous system (CNS), acute pulmonary, and chronic pulmonary oxygen toxicity. This study identifies acute and chronic CNS oxygen toxicity under 2.0 atmospheres absolute (ATA) pressure of oxygen. Methods: The authors’ medical records from September 29, 1989 to January 20, 2023 and correspondence to the authors (9/1994 to 1/20.2023) from patients with signs and/or symptoms historically identified as acute CNS oxygen toxicity and those with neurological deterioration receiving hyperbaric oxygen for neurological conditions were reviewed. Acute cases were those occurring with ≤5 HBOTs and chronic cases >5 HBOTs. Chronic cases were separated into those at 1.5 ATA, > 1.5 ATA, or < 1.5 ATA oxygen. Cumulative dose of oxygen in atmosphere-hours (AHs) was calculated at symptom onset. Results Seven acute cases, average 4.0 ± 2.7 AHs, and 52 chronic cases were identified: 31 at 1.5 ATA (average 116 ± 106 AHs), 12 at >1.5 ATA (103 ± 74 AHs), and 9 at <1.5 ATA (114 ± 116 AHs). Second episodes occurred at 81 ± 55, 67 ± 49, and 22 ± 17 AHs, and three or more episodes at 25 ± 18, 83 ± 7.5, and 5.4 ± 6.0 AHs, respectively. Most cases were reversible. There was no difference between adults and children (p = 0.72). Acute intervention in cases (<3 months) was more sensitive than delayed intervention (21.1 ± 8.8 vs. 123 ± 102 AHs, p = 0.035). Outside sources reported one acute and two chronic exposure deaths and one patient institutionalized due to chronic oxygen toxicity. A withdrawal syndrome was also identified. Conclusion Hyperbaric oxygen therapy-generated acute and chronic cases of CNS oxygen toxicity in chronic neurological conditions were identified at <2.0 ATA. Chronic CNS oxygen toxicity is idiosyncratic, unpredictable, and occurred at an average threshold of 103–116 AHs with wide variability. There was no difference between adults and children, but subacute cases were more sensitive than chronic intervention cases. When identified early it was reversible and an important aid in proper dosing of HBOT. If ignored permanent morbidity and mortality resulted with continued HBOT.